PS02.042: PROGNOSTIC ROLE OF HPV INFECTION IN ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (14th September 2018) - Bognar, Laura; Bellyei, Szabolcs; Hegedus, Ivett; Gombos, Katalin; Horvath, Ors; Vereczkei, Andras; Pozsgai, Eva; Papp, Andras
Abstract: Background: The aims of this study were to evaluate whether HPV infection has a prognostic role in patients with esophageal squamous cell carcinoma who underwent oncological treatment and also to correlate the heat shock proteins (Hsp) 90, 27 and 16.2 and growth hormone-releasing hormone receptor (GHRH-R) expression patterns of the pre-treatment tumor biopsies with the HPV status and with the oncological response. Methods: Pre-treatment tumor biopsies of 74 patients with locally advanced esophageal squamous cell carcinoma were processed retrospectively. The presence of HPV was detected by chromogenic in situ hybridization. Hsp and GHRH-R expressions were determined using immunohistochemistry. Following neoadjuvant or definitive radiochemotherapy, the patients were restaged according to the Response Evaluation Criteria in Solid Tumors. The correlation between the HPV status, response and Hsp and GHRH-R expressions were evaluated. Results: Fourteen (19%) patients were HPV-positive. HPV-positive patients were more likely to respond poorly to multimodal therapy (71.4% were non-responders vs. 28.6% responders) and had shorter overall survival compared to HPV-negative patients (median survival of 6 months vs. 7 months), although the difference was not significant (Log Rank P  = 0.898). A significantly higher number of HPV-positive patients expressed Hsp 90 and 16.2 at high levels (85.7% and 71.4%, respectively) than at low levels. Higher levels of Hsp expressions resulted in poorer response to therapy and worse overall survival. Conclusion: We found that HPV infection resulted in poor response to therapy and decreased overall survival, and therefore proved to be a negative prognostic factor in patients with esophageal squamous cell carcinoma. There was a linear correlation between levels of Hsp 90 and 16.2 expression and HPV positivity. Disclosure: All authors have declared no conflicts of interest.